Multi-Watt Simultaneous Orthogonally Polarized Dual-Wavelength Pulse Generation of an Intracavity Nd:YLF/YVO4 Raman Laser - Zhiyu Zuo; Shibo Dai; Hao Yin; Siqi Zhu; Zhen Li; Zhenqiang Chen; Yi Zheng; Guiyao Zhou (IEEE Photonics Journal, 2019)
We present the first demonstration of an actively Q-switched orthogonally polarized dual-wavelength Nd:YLF/YVO4 Raman laser to our knowledge. The gain competition of the orthogonally polarized dual-wavelength fundamental laser at 1047 and 1053 nm was ultimately avoided by incorporating two Nd:YLF crystals into two laser resonators. By adjusting the gain or loss difference of two resonators, the pulse synchronization of the orthogonally polarized dual-wavelength Raman laser was realized. Benefitting from the efficient thermal stress and energy-transfer upconversion management of Nd:YLF crystal, a maximum dual-wavelength Raman output power of 4.5 W was obtained with M2 <; 1.8, which contained a 2.5 W Raman component at 1155 nm and a 2.0 W Raman component at 1162 nm, under the incident pump power of 46.1 W and pulse repetition frequency of 5 kHz. The corresponding peak powers were as high as 178.6 and 142.9 kW, respectively. As far as we know, we have increased the orthogonally polarized dual-wavelength Raman average output power by six times.